Imam Shafi'i's Educational Thought And Its Implications For Contemporary Islamic Education - Mukhsin Mukhsin; Ilzam Hubby Dzikrillah Alfani (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
This study discusses the educational thought of Imam Shafi'i, exploring the fundamental concepts he offered and analyzing their implications for contemporary Islamic education. The research employs a qualitative approach with a literature review method. Imam Shafi'i emphasized the importance of a curriculum that fosters noble character, beneficial knowledge, and the integration of knowledge with faith. He stressed the need for educators to possess total commitment and integrity, for students to respect their teachers, and for a supportive environment for the educational process. He also advocated for a systematic approach to understanding the Qur'an and Hadith, as well as the development of intellectual and ethical capacities. The implications of these thoughts include the importance of a curriculum based on authentic sources that are relevant to the needs of the times and the role of educators as role models in ethics and morality. The relevance of Imam Shafi'i's thought in addressing the challenges of Islamic education in the modern era and globalization lies in his systematic approach, which can be adapted to modern educational technology, as well as his emphasis on the integration of knowledge and religion, character building, and the balance between worldly and spiritual knowledge. This abstract demonstrates that Imam Shafi'i's educational thought remains relevant and provides a strong foundation for the development of Islamic education amidst global dynamics.